Approximate Solutions Of Chemical Reaction - Diffusion Brusselator System And Coupled Schrodinger - Kdv Equation Using New Iterative Method - M. KARTHIVEL, M. K. SIVASANKARI, (International Journal of Modern Agriculture, 2021)
This article, presents the approximate solutions of Chemical Reaction-Diffusion Brusselator system and Coupled Schrodinger – Korteweg - de Vries equation by a reliable algorithm of New Iterative Method. Results obtained by proposed method are compared with exact solutions as well as with the results obtain by Optimal Homotopy Asymptotic Method, Homotopy Perturbation Method and Variational Iterational Method. New Iterative Method is an improvement with regard to its accuracy and rapid convergence. Since mathematical analysis leads to Brusselator equations for some chemical reaction-diffusion experiments, it is worth demanding a new technique to solve such a method. We are creating a modern and successful recurring method. Numerical results indicate that the approach suggested is accurate and efficient. The method's precision increases with the number of iterations increasing.